SÍNTESE E CARACTERIZAÇÃO DO ÓXIDO MISTO Fe/Ti E SUA APLICAÇÃO EM FOTOCATÁLISE HETEROGÊNEA - Ignachewski, Franciély (2014)
This work presents the achievement of mixed oxides` Fe/Ti by Sol/Gel processing method. However, it is not intended to promote the doping of materials but a synthesis in-situ of a specific phase of the iron titanate or pseudobrookite (Fe2TiO5), which is considered a great catalytic. The procedure consists in dissolving iron salt in alcohol and a further addition of titanium alkoxy followed by heat treatment. Two synthetic routes have been used and in one of them were used titanium isopropoxide, propanol and ferric chloride as precursors. In the other one the precursors were titanium butoxide, butanol and ferric chloride. The materials obtained were synthesized with 0%, 25%, 50% and 75% of iron. The study reports that the achievement of mixed oxides` can be obtained by both routes and also a specific mixed oxides` phase, the pseudobrookite, can be detected. By studying the characterization of materials we could found very different phases which were confirmed in the DRX, Raman spectroscopy and at the infra-red region. In the iron-containing materials the formation of a single iron titanate, or psedobrookite, it is obvious as well as a mixture of the rutile, anatase and hematite phases. The XAS (X-Ray AbsorptionSpectroscopy) has also provided data concerning the local chemical structure of the iron and titanium atoms. The results obtained by the XAS proved that the iron atoms are incorporated in the anatase`s structure, replacing the titanium atoms. This replacement promotes distortion in the anatase`s octahedral structure. The products of the synthesis have industrial application in the effluents` treatment of various sources (textiles, paper-makers, among others). These materials applied in the photo degradation present high commercial value,since in a short term eliminate problems with residues that could be very harmful to the environment if were released.